Development of UTHM's Airship Virtual Simulator - Hariri, Azian; Sebayang, Darwin; Wibowo, Ignatius Agung (International Journal of Integrated Engineering, 2022)
Airship virtual simulator was developed by programming the solution of the airship equations of motion to Matlab GUI. This paper shows a case study done by applying the physical data of a designed airship called ‘UTHM’s Airship’ in the airship equations of motion for development of airship virtual simulator. In this study, the approximate and calculated stability modes of the designed airship were compared for validation purposes. The virtual simulator operates by selecting the desired control angle of elevator, rudder or vectored thrust as input and the response outputs are shown in motion of pitch, yaw or roll angle through a moving airship figure in the simulator. At the end of this paper, the virtual simulator had successfully helped interprets the response of the designed airship into an interesting and easy to understand visualization.